Epidermal growth factor enhances osteogenic differentiation of dental pulp stem cells in vitro - Del Angel Mosqueda, Casiano; Gutiérrez Puente, Yolanda; López Lozano, Ada Pricila; Romero Zavaleta, Ricardo Emmanuel; Mendiola Jiménez, Andrés; Medina de la Garza, Carlos Eduardo; Márquez M, Marcela; De la Garza Ramos, Myriam Angélica (2015)
Introduction: Epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF) play an important role in extracellular matrix mineralization, a complex process required for proper bone regeneration, one of the biggest challenges in dentistry. The purpose of this study was to evaluate the osteogenic potential of EGF and bFGF on dental pulp stem cells (DPSCs). Material and methods: Human DPSCs were isolated using CD105 magnetic microbeads and characterized by flow cytometry. To induce osteoblast differentiation, the cells were cultured in osteogenic medium supplemented with EGF or bFGF at a low concentration. Cell morphology and expression of CD146 and CD10 surface markers were analyzed using fluorescence microscopy. To measure mineralization, an alizarin red S assay was performed and typical markers of osteoblastic phenotype were evaluated by RT-PCR. Results: EGF treatment induced morphological changes and suppression of CD146 and CD10 markers. Additionally, the cells were capable of producing calcium deposits and increasing the mRNA expression to alkaline phosphatase (ALP) and osteocalcin (OCN) in relation to control groups (p < 0.001). However, bFGF treatment showed an inhibitory effect. Conclusion: These data suggests that DPSCs in combination with EGF could be an effective stem cell-based therapy for bone tissue engineering applications in periodontics and oral implantology.